Profitability, Capital Intensity, and Company Size against Tax Avoidance with Leverage as an Intervening Variable - Nabila Zhafira Sofiamanan; Zaky Machmuddah; Natalistyo T.A.H (Journal of Applied Accounting and Taxation, 2023)
This study aims to determine whether profitability, capital intensity, and company size, directly and indirectly, affect tax avoidance with leverage as an intervening variable in financial sector companies listed on the Indonesia Stock Exchange (IDX). The year 2018-2021 is used as an observation period. Purposive sampling was chosen as a sample sorting method with the results of a study of 106 companies with 269 observation data. This type of research is quantitative using WarpPLS 8.0. The research results are that profitability, capital intensity, and company size directly affect tax avoidance, and profitability and company size indirectly affect tax avoidance through the leverage of intervening variables. However, the capital intensity does not indirectly affect tax avoidance through leverage as an intervening variable. The implication of this study is the importance of doing tax planning for companies.